Gait analysis in dogs with pelvic fractures treated conservatively using a pressure-sensing walkway - Vassalo, Flávia Gardilin; Rahal, Sheila Canevese [UNESP]; Agostinho, Felipe Stefan; Mamprim, Maria Jaqueline [UNESP]; Melchert, Alessandra [UNESP]; Kano, Washington Takashi; dos Reis Mesquita, Luciane; Doiche, Danuta Pulz (Springer Nature, 2015)
This study aimed to evaluate dogs with pelvic fractures and treated conservatively during locomotion on a pressure-sensing walkway. The hypothesis was that dogs may present changes in kinetic and temporospatial parameters because of the fractures, which may interfere with the symmetry index. Thirty dogs were selected and divided into two groups: Group 1-healthy group (n = 15) and Group 2-conservatively treated group (n = 15). The dogs were of similar body size. The body weight distribution percentages and symmetry indices of the peak vertical force, vertical impulse, stance time, swing time, percentage of stance time, and percentage of swing time of the hind limbs were evaluated. In Group 2, the time interval between fracture occurrence and patient evaluation was between 4 and 87 months (mean of 20 months). Four dogs had lower percentage of body weight distribution on one of the hind limbs while three dogs had greater weight distributed toward both hind limbs. Four of these dogs had alterations in the temporospatial and/or kinetic symmetry indices. Dogs with pelvic fractures treated conservatively may present changes in percentage of body weight distribution and symmetry indices of the kinetic and temporospatial parameters. The conservative treatment can cause persistent abnormal gait.